Feasibility and effectiveness of laparoscopic transgastric stapler assisted circumferential esophageal mucosectomy and simultaneous fundoplication in a pig model - Steinemann, Daniel; Müller, Philip C.; Schwarz, Anne-Catherine; Zerz, Andreas; Linke, Georg R.; Müller, Beat P. (Diseases of the esophagus, 2018)
Laparoscopic transgastric stapler assisted mucosectomy (SAM) has been described for minimally invasive circumferential en-bloc resection of Barrett’s esophagus (BE). Conceivably long-term disease control might be achieved by adding anti-reflux surgery after resection of BE by SAM. The aim of this study was to assess the feasibility of combined SAM and fundoplication in one laparoscopic procedure in 6 pigs. Furthermore, the competence of the gastroesophageal junction (GEJ) was assessed at baseline, after SAM, and after subsequent laparoscopic fundoplication. At each measuring point reflux measurements were repeated 6 times in each pig. Blue-colored water was infused into the stomach for provocation of reflux. Intragastric yield pressure and volume until drainage of blue solution (DBS) were recorded. Time to reflux by DBS and by multichannel intraluminal impedance (MII) was measured. Laparoscopic fundoplication after SAM was feasible in all animals in a single-session. A weakening of the GEJ was found after SAM, indicated by decreased yield pressure, yield volume, time to DBS and MII (p=0.007, p<0.001, p<0.001 and p=0.008). After adding a Nissen-fundoplication the GEJ was restored. The measurements of the competence of the GEJ returned to baseline values. (Yield volume, p=0.11; time to DBS, p=0.15; MII p=0.84). The yield pressure increased from 11.5 mmHg at baseline to 19.7 mmHg after SAM and fundoplication (p<0.001). Laparoscopic fundoplication and SAM may be combined in a single laparoscopic session. Although weakened after SAM Nissen fundoplication restored the GEJ as an effective reflux barrier in this experiment. Clinical validation is needed to confirm the results in a prospective human trial.
Gesehen am 14.04.2020